2010
DOI: 10.1080/09540121003623701
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of lifetime suicidal ideation among HIV-infected male inmates in Taiwan

Abstract: The purpose of this study was to explore the prevalence and correlates of lifetime suicidal ideation (SI) among HIV-infected male inmates. All participants in seven prisons, comprising roughly 20% of all HIV-infected male inmates in Taiwan, were stratified by geographic location and surveyed using a self-administered, anonymous questionnaire. The five-item Brief Symptom Rating Scale (BSRS-5) was used on 535 participants to measure various dimensions of psychological distress. Seven questions regarding lifetime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 33 publications
2
8
4
Order By: Relevance
“…Whereas the current finding on prevalence of suicidal attempt were higher than a study conducted in Taiwan among HIV-infected male inmates i.e. (4.1%) [26], in Australia young prisoners (3.6%) [11] and in Great Britain (4.4%) [22]. This difference might be attributed to difference in study subjects in which Taiwan study used only male prisoners and great British used female prisoners and sampling Note: α=0.05, * P-value<0.05, **P-value<0.01, ***P-value<0.001 Note: α=0.05, * P-value<0.05, **P-value<0.01, ***P-value<0.001 technique which was stratified sampling with 535 inmates.…”
Section: Variablescontrasting
confidence: 92%
See 2 more Smart Citations
“…Whereas the current finding on prevalence of suicidal attempt were higher than a study conducted in Taiwan among HIV-infected male inmates i.e. (4.1%) [26], in Australia young prisoners (3.6%) [11] and in Great Britain (4.4%) [22]. This difference might be attributed to difference in study subjects in which Taiwan study used only male prisoners and great British used female prisoners and sampling Note: α=0.05, * P-value<0.05, **P-value<0.01, ***P-value<0.001 Note: α=0.05, * P-value<0.05, **P-value<0.01, ***P-value<0.001 technique which was stratified sampling with 535 inmates.…”
Section: Variablescontrasting
confidence: 92%
“…This was in line with a study done at New south Wales Australia (AOR=3.06) [10]. This was also supported by studies done at British and Taiwan prisons [26,40]. This could be due to the fact that depressed individual have neurotransmitter disturbance in the brain which may contribute for hopelessness, guilty, worthlessness, and this intern leads to suicidal behavior [34].…”
Section: Factors Associated With Suicidal Behavior Among Prisonerssupporting
confidence: 86%
See 1 more Smart Citation
“…Existing cross-sectional work indicates a potential relationship between anxiety and suicidal thoughts, behaviors, and attempt history among PLWHA. For instance, one study examined 535 Taiwanese inmates (Peng et al, 2010) and indicated that psychological distress (including symptoms of anxiety or tension) predicted serious thoughts of suicide. Another cross-sectional study conducted by researchers in Uganda indicated that GAD was related to suicidal thoughts, plans, preparation, and previous attempts (coded together as a measure of overall suicidality) (Kinyanda, Hoskins, Nakku, Nawaz, & Patel, 2012).…”
Section: Anxiety and Its Disorders In Relation To Hiv/aids Clinicamentioning
confidence: 99%
“…Compared with the general population, HIVpp are 2–7‐fold more likely to meet the diagnostic criteria for MD in accordance with international classification systems (DSM‐IV or ICD‐10), while MD prevalence rates range from 18% to 81%, depending on the subjects . Most studies, however, have not used strict diagnostic criteria, according to DSM‐IV or ICD‐10, but have relied on physician reporting or structured screening surveys .…”
Section: Epidemiologymentioning
confidence: 99%